Impact of age on survival in radioiodine refractory differentiated thyroid cancer patients. Issue 5 (May 2021) - Saïe, C; Wassermann, J; Mathy, E; Chereau, N; Leenhardt, L; Tezenas du Montcel, S; Buffet, C
Abstract : Objective: The objectives of our study were to analyze the influence of age on the survival of patients with RAIR-DTC and to determine their prognostic factors according to age. Methods: This single-center, retrospective study enrolled 155 patients diagnosed with RAIR-DTC. The primary end point was overall survival (OS) according to different cutoff (45, 55, 65, 75 years). Secondary endpoints were progression free survival (PFS) and prognostic factors in patients under and over 65 years. Results: Median OS after RAIR diagnosis was 8.2 years (95% IC: 5.3–9.6). There was no difference according to age with a 65 ( P  = 0.47) and 55 years old cutoff ( P  = 0.28). Median OS improved significantly before 45 years old ( P  = 0.0043). After 75 years old, median OS significantly decreased ( P  = 0.0008). Median PFS was 2.1 years (95% CI: 0.8–3) in patients < 65 years old, and 1 year in patients ≥ 65 years old (95% CI: 0.8–1.55) with no statistical difference ( P  = 0.22). There was no impact of age on PFS with any cutoff. In both groups, progressive disease despite 131 I treatment reduced OS. In patients < 65 years old, an interval of less than 3 years between the initial diagnosis and the diagnosis of RAIR metastatic disease was predictive of poor survival. In patients > 65 years old, the presence of a mediastinum metastasis was a significant factor for mortality (HR: 4.55, 95% CI: 2.27–9.09). Conclusion: In RAIR-DTC patients, a cut-off age of 65 years old was not a significant predictive factor of survival. Forty-five and 75-years-old cutoff were predictive for OS but not PFS.